Relationship Classification in Large Scale OSN and its Impact on Information Propagation - Tang, Shaojie; Yuan, Jing; Mao, Xufei; Li, Xiang-Yang; Chen, Wei; Dai, Guojun (In Proceedings of the 30th IEEE International Conference on Computer Communications (INFOCOM'2011), Shanghai, China, April, 2011., 2011)
In this paper, we study two tightly coupled topics in online social networks (OSN): relationship classiﬁcation and information propagation. The links in a social network often reﬂect social relationships among users. In this work, we ﬁrst investigate identifying the relationships among social network users based on certain social network property and limited preknown information. Social networks have been widely used for online marketing. A critical step is the propagation maximization by choosing a small set of seeds for marketing. Based on the social relationships learned in the ﬁrst step, we show how to exploit these relationships to maximize the marketing efﬁcacy. We evaluate our approach on large scale real-world data from Renren network, showing that the performances of our relationship classiﬁcation and propagation maximization algorithm are pretty good in practice.